Emerging East-West corporate networks in Central European border regions: Some theoretical arguments and stylized facts - Katja Gerling; Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
Economic re-integration after a long period of separation among countries with different levels of development is expected to start in border regions. Enterprises along the borderline can gain a rent due to low transport and transaction costs. They benefit from the fortunate opportunity of tapping the international division of labour on the shortest distance. Therefore, border regions should be predestined to become an economic powerhouse. Despite their great potential, border regions in Central Eastern Europe are far from being an economic entity. The enormous development differences are obviously a source of constraint rather than an impetus to integration. This paper examines the potential for cross-border activities on the German- Polish border. It - first, sketches the theoretical background, - second, presents some facts and figures, and - third, discusses the key policy question of how to overcome the obstacles to closer co-operation. The paper comes to the conclusion that close cross-border co-operation, which can be labelled as a network, is still the exception rather than the rule in the region under consideration. Most of the activities can be ranged in the category of simple subcontracting arrangements in which the German partners exploit the low wage, energy and pollution control costs beyond the border.
Keywords: D2; F2; P52; 330; Grenzgebiet; Unternehmensnetzwerk; Internationale Wirtschaftsbeziehungen; Entwicklungskonvergenz; Regionalpolitik; Deutschland; Polen; Mitteleuropa